Mathematical economics : - Dowling, Edward T. (McGraw-Hill, 2006)
Publisher description for Mathematical economics / by Edward T. Dowling ; abridgement editor, Kenneth Dutch ; based on Schaum's outline of theory and problems of mathematical methods for business and economics.